DIGITAL TECHNOLOGIES IN THE STRUCTURE OF SOCIAL BEING AND THE DIMENSIONS OF SECURITY - Sokolovskyi, Oleh; Lysetska, Yuliiа (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2026)
Digital technologies are driving profound transformations of social being, reshaping the ways in which interaction, institutional activity, and security are organized. They create new conditions for social predictability while simultaneously generating risks of informational vulnerability and digital inequality. As a result, security acquires an ontological dimension in the functioning of сontemporary society. The aim of the article is to provide a philosophical analysis of the impact of digital technologies on the structure of social being and to conceptualize the transformation of security within the context of digital reality. Research methods. The study is grounded in the approaches of social philosophy and the philosophy of technology, employing systemic, hermeneutic, and analytical-prognostic methods to identify the interconnections among technological, institutional, and social processes. Research results. It is substantiated that the automation of governance processes, big data analytics, and artificial intelligence contribute to the formation of a cognitively oriented model of institutional action in which forecasting, analytical justification of decisions, and the capacity to operate under conditions of uncertainty acquire primary importance. Digital technologies enhance governmental transparency and institutional legitimacy, facilitate the rational allocation of resources, and improve the efficiency of public services. Discussion. At the same time, the technological mediation of social processes foregrounds the problem of responsibility for algorithmic decisions, intensifies concerns regarding cybersecurity, and reveals the risks of digital inequality that affect levels of institutional trust. It is demonstrated that security assumes a multidimensional character, encompassing informational, social, and institutional levels while becoming increasingly integrated into the very structure of social being. Conclusions. Digital technologies function as a driver of the reorganization of the social order, within which security becomes a normative orientation of societal development. Institutional effectiveness is determined by the capacity to integrate technological innovations into a system of value orientations, aligning technical progress with the principles of responsibility, trust, and the preservation of human dignity.